(untitled) (Medico Legal Update, 2020)
COVID-19 has put the globe in an unforeseen and unexpected situation. COVID-19 has affected everyday life all over the world. Human population came face to face to this virus so gravely for the first time. During the initial days nearly all countries imposed lockdown to break the chain of viral spread. This created significant knock-on effects on the daily life of citizens. With the updates on COVID-19, the guidelines issued by medical authorities, categorized geriatric and paediatric age groups to be at high risk. In order to flatten the rising curve of exponential spread of the virus ban on gatherings resulted in enforced shut down of schools. Therefore children were bound to stay home. They were automatically exposed to the over use of electronic gadgets for recreation as well as education purpose .Hence, their screen time increased many fold. This paper describes the impact of COVID-19 and use of electronic screen on children.